COMMITMENT TO PROFESSION IN UNIVERSITY STUDENTS: RELATIONS TO PERSONALITY TRAITS AND SATISFACTION WITH STUDIES - Pociūtė, Birutė; Bulotaitė, Laima; Bliumas, Remigijus (Acta Paedagogica Vilnensia, 2012)
The cognitive, psychosocial and career development is important for an efficient education. Students’ readiness to become successful in their profession is one of the most important goals for the universities not only in the realization of academic goals, but also in making the commitment to their profession. The aim of this investigation was to reveal features of commitment to profession and its relations to the satisfaction with studies and to personality traits in university students. The results show that satisfaction with studies is high enough in students, and it is positively related to their emotional commitment to the profession. Also, independently of the study program and course, there are significant relations between emotional commitment to the profession, job satisfaction and personality traits, such as conscientiousness, openness, and agreeableness. Continuing commitment to the profession is not significantly related to satisfaction with studies, but significantly correlates with neuroticism.
Keywords: commitment to profession; university students; personality traits; satisfaction with studies; relations